Rereading Austen: from XIX century young lady hero to XXI century vlogger - Amorim, Maria Inês Freitas de (Lumina - Revista do Programa de Pós-Graduação em Comunicação da Universidade Federal de Juiz de Fora, 2015)
Pride and Prejudice, the novel authored by English writer Jane Austen, may be considered one of the well-remembered novels from the history of literature. Even though it has been two centuries since its publication, the narrative presents discussions that reverberate nowadays, such as the social role of women and criticisms to a society that privileges appearances. The novel has been adapted several times to various formats such as film, television series or reread onto other literary works. The first attempt to adapt it for the internet is the webseries The Lizzie Bennet Diaries, 2012,broadcasted on a channel on youtube.com. The webseries also created characters’ profiles on social media such as Twitter, Facebook and Tumblr, allowing audience interaction. One hundred episodes were produced in an effort to bring a contemporary view of the novel by presenting a new post from the main character’s vlog at each episode. This article aims to analyze which elements of literary narrative were preserved with this particular adaptation of the novel to a webseries considering the necessary contextualization to maintain verisimilitude.